I kølvandet - levedygtighed og koloniale økologier ved havnen på St. Thomas - Brichet, Nathalia; Hastrup, Frida (Slagmark - Tidsskrift for idéhistorie, 2017)
IN THE WAKE – LIVEABILITY AND COLONIAL ECOLOGIES AROUND THE HARBOUR OF ST THOMAS Setting out to prepare an exhibition at the Maritime Museum in Denmark in commemoration of the centennial for the Danish selling of the Virgin Islands to the USA in 1917, we explore what follows in the wake of more than 200 years of Danish ownership of the West Indian Islands, as they were then termed. The harbour in Charlotte Amalie is the article’s central analytical unit, and with a point of departure in this harbour we discuss how the former colonial presence has left its marks on the islands’ ecologies and nurtured both wondrous and monstrous forms of life. We ask a rather open question: How do past industrial activities in and around the harbour of Charlotte Amalie on the island of St. Thomas emerge and ramify today? The guiding idea for the exhibition and for this article is to engage stories and objects from present day life in the Charlotte Amalie harbour made possible – directly or indirectly – by Danish presence, bearing its mark in one way or another.